2008
DOI: 10.1016/j.physleta.2007.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Local basis-dependent noise-induced Bell-nonlocality sudden death in tripartite systems

Abstract: We demonstrate that multipartite Bell-inequality violations can be fully destroyed in finite time in three-qubit systems subject only to the mechanism of local external asymptotic dephasing noise. This broadens the study of local-noise-induced sudden death of nonlocal behavior, extending it beyond the realm of bipartite systems, to which it had previously been restricted.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…5, the strong coupling g ¼ 10 is analyzed. We find that the Bell violation is destructed completely in a finite time and such a phenomenon is called Bell violation sudden death [29]. Under weak coupling, the Bell violation decreases fast initially and tends to oscillates around a same stable value for different values of DM interaction.…”
Section: Bell Violationmentioning
confidence: 85%
See 3 more Smart Citations
“…5, the strong coupling g ¼ 10 is analyzed. We find that the Bell violation is destructed completely in a finite time and such a phenomenon is called Bell violation sudden death [29]. Under weak coupling, the Bell violation decreases fast initially and tends to oscillates around a same stable value for different values of DM interaction.…”
Section: Bell Violationmentioning
confidence: 85%
“…[30]. It should be noted that the formulations in [29] does not demonstrate the Bell violation of the GHZ entangled state.…”
Section: Bell Violationmentioning
confidence: 88%
See 2 more Smart Citations
“…Very recently, Jaeger and Ann [14] demonstrated the Bell-nonlocality sudden death (BNSD) of tripartite system by analyzing Bell-inequality violations. It is showed that multipartite Bell-inequality violations can be fully destroyed in finite time in three-qubit systems subject to the multi-local asymptotic dephasing noise.…”
Section: Introductionmentioning
confidence: 99%